Ocular Involvement in Sarcoidosis - Groen, Fahriye; Rothova, Aniki (Seminars in Respiratory and Critical Care Medicine, 2017)
Ocular involvement in sarcoidosis occurs in ∼40% and the eye is the presenting organ in roughly 20%. The course of ocular disease does not necessarily parallel that of systemic disease. Uveitis is the most common presentation and shows mainly a chronic course; anterior uveitis is associated with better visual prognosis than posterior localization. Painful bilateral anterior granulomatous uveitis most commonly occurs in black patients at younger age, while painless posterior bilateral involvement with peripheral multifocal choroiditis is commonly seen in elderly white females. Patients with posterior uveitis develop often ocular complications and central nervous system involvement. Vitritis, segmental periphlebitis, choroidal granulomas, and peripheral multifocal chorioretinitis are often seen clinical features. Optic nerve involvement is uncommon, but if present, results often in poor visual outcome. Lacrimal gland and conjunctival involvement are also common and present clinically as dry eyes or remain asymptomatic with good visual prognosis. Sarcoidosis-associated uveitis is mostly managed by local treatment with steroid drops or periocular and intraocular steroid injections or with novel intraocular corticosteroid implants. Patients with sight-threatening disease or optic nerve involvement need systemic therapy. Systemic therapy is based on a step-up regimen where corticosteroids are used in the initial phase of the disease and if long-term treatment is required, steroid-sparing immunomodulatory drugs are implemented such as methotrexate or biological agents. Despite the mainly chronic course, need for long-term treatment, and frequent ocular surgeries in the majority of patients, the visual outcome of sarcoidosis-associated uveitis is fairly good if therapy has started on time.
Keywords: sarcoidosis; ocular sarcoidosis; sarcoidosis-associated uveitis; lacrimal gland involvement; treatment ocular sarcoidosis; diagnosis of ocular sarcoidosis